2013
DOI: 10.1007/s12630-013-9934-6
|View full text |Cite
|
Sign up to set email alerts
|

Proximal aortic compliance and diastolic function assessed by speckle tracking imaging

Abstract: Purpose Speckle tracking imaging (STI) is a recent technique that evaluates an echocardiographic image throughout the cardiac cycle and provides dynamic variables such as tissue velocities and strain rates. The objective of our study was to determine 1) if STI can be used to quantify proximal aortic compliance and 2) if decreased aortic compliance determined by STI will reproduce the previously reported correlation with diastolic function. Methods This was a retrospective observational case series using previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
6
0
1
Order By: Relevance
“…Adult studies have demonstrated that increased pulse pressure (a crude surrogate for arterial stiffness) is independently predictive of not only diastolic dysfunction ( 15 17 ) but also heart failure with preserved ejection fraction ( 18 , 19 ). In addition, carotid artery wall stiffness ( 20 , 21 ) and aortic compliance, a similar parameter, positively correlate with LV diastolic function ( 22 ). Similar to our results, increased PWV is independently associated with diastolic dysfunction in patients with hypertension ( 23 ), type 2 diabetes ( 24 ), clustered CV risk factors ( 25 ), and suspected coronary artery disease ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Adult studies have demonstrated that increased pulse pressure (a crude surrogate for arterial stiffness) is independently predictive of not only diastolic dysfunction ( 15 17 ) but also heart failure with preserved ejection fraction ( 18 , 19 ). In addition, carotid artery wall stiffness ( 20 , 21 ) and aortic compliance, a similar parameter, positively correlate with LV diastolic function ( 22 ). Similar to our results, increased PWV is independently associated with diastolic dysfunction in patients with hypertension ( 23 ), type 2 diabetes ( 24 ), clustered CV risk factors ( 25 ), and suspected coronary artery disease ( 26 , 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dr. A. Gregory et al from the University of Calgary reports on the utility of TEE to calculate aortic compliance and ventricular mechanics using relatively new ''speckle tracking'' software in combination with a blood pressure trace. 5 This is a further demonstration of the increasing potential for ultrasound in clinical practice. It is also obvious that further research is required before this methodology can be employed; however, this study shows feasibility in the clinical context.…”
mentioning
confidence: 80%
“…Dr A. Gregory et coll., de l'Université de Calgary, décrivent l'utilité de l'É TO pour calculer la compliance aortique et la mécanique ventriculaire à l'aide d'un logiciel de 'suivi de pixel' relativement nouveau, combiné à un tracé de la tension artérielle. 5 Il s'agit ici d'une autre démonstration du potentiel grandissant de l'échographie dans la pratique clinique. Il est également évident que des recherches supplémentaires seront nécessaires avant que cette méthodologie ne puisse être employée; toutefois, cette étude montre la faisabilité d'une telle application dans le contexte clinique.…”
unclassified
“…STI analysis was further applied to the ascending aorta using the EchoPac software's pre-set for two-chamber LV images using a method we have previously described [4]. This method includes adjusting the software's pre-set spatial and timing filters to the lowest level.…”
Section: Speckle-tracking Echocardiographymentioning
confidence: 99%
“…Elevated measures of arterial stiffness (central and peripheral) have been shown to negatively impact LV systolic and diastolic function, impair coronary blood flow, and have been identified as a risk factor for cardiovascular disease and mortality [1][2][3][4][5][6][7][8][9]. One possible mechanism for these findings is that increased arterial stiffness can create additional LV work while simultaneously making coronary perfusion less efficient.…”
Section: Introductionmentioning
confidence: 99%